2018
DOI: 10.1080/13683500.2017.1423283
|View full text |Cite
|
Sign up to set email alerts
|

The solo female Asian tourist

Abstract: This qualitative study explores the travel motivations and experiences of solo female Asian tourists. Data were collected from ten in-depth interviews with a focus on Asian women's travel motivations, experiences and constraints. Thematic analysis was used to analyse the data. Resistance was found to be an important factor as in order to travel solo, the participants had to resist sociocultural expectations for Asian women's behaviour. Sexualized male attention was also found to be an important constraint. Suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 69 publications
8
72
1
6
Order By: Relevance
“…We wound up chatting throughout the night with another couple and had a very pleasant, casual evening.For solo‐traveling tourists, social interaction at dining time is even identified as a major attraction for them to attend private social dining. This group of tourists may prefer to travel alone without partners from a familiar context, but they occasionally need to relieve their loneliness during travel and make them have a sense of being (Bianchi, 2016; Seow & Brown, 2018). At this time, private social dining performs such a function to provide solo tourists a chance to reconnect with the society.
This was my first time in Paris and first time traveling solo.
…”
Section: Findings and Discussionmentioning
confidence: 99%
“…We wound up chatting throughout the night with another couple and had a very pleasant, casual evening.For solo‐traveling tourists, social interaction at dining time is even identified as a major attraction for them to attend private social dining. This group of tourists may prefer to travel alone without partners from a familiar context, but they occasionally need to relieve their loneliness during travel and make them have a sense of being (Bianchi, 2016; Seow & Brown, 2018). At this time, private social dining performs such a function to provide solo tourists a chance to reconnect with the society.
This was my first time in Paris and first time traveling solo.
…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In criminal hostile behaviors, tourists are exposed to a great risk of harm particularly within the context of physical aggression. Aggression toward tourists includes sexual harassment (Jordan & Aitchison, ; Seow & Brown, ), aggressive selling (Kozak, ; McElroy, ; Nicely & Ghazali, ), and drug peddling (de Albuquerque & McElroy, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the specific subject of aggressive harassment, emerging studies identify sexual harassment as a common but least‐reported tourist experience (Brown & Osman, ; Calafat et al, ). Seow and Brown () have likewise argued that sexualized male gaze is a major constraint for solo female travelers. These authors also draw attention to the subjective assessment of sexual harassment, often arguing that it is complex because behaviors perceived as sexual harassment differ across cultures, individuals, contexts, and moments of time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These constructions of vulnerability have implications for, and likely some basis in, women's and men's travel experiences, as women often report negative experiences, including harassment, fear, and anxiety (e.g., Burek and Kolbl-Ebert 2007;Heimtun 2012;Heimtun and Abelsen 2013;Seow and Brown 2018;Small 2016;Thomas and Mura 2019;Wilson and Little 2008). For example, an interview study of 52 solo women travelers found that many women reported fearing and experiencing harassment from men, often describing attempts to reduce it, such as selecting clothing to deflect unwanted attention.…”
Section: Gender Patterns In Solo Travelmentioning
confidence: 99%
“…As a gendered constraints perspective highlights, women have not, in most times and places, been as free as men to explore new environments, particularly as autonomous travelers (Khoo-Lattimore and Wilson 2017; Wilson and Little 2005). This conclusion receives support from studies examining women's and men's solo travel experiences, which often reveal women's heightened concerns regarding their safety, as well as their more frequent reports of negative experiences like harassment (Heimtun 2012;Seow and Brown 2018). In contrast with the more extensive literature on the experiences of women and men traveling alone, less attention has been given to gendered constructions of these travelers in media targeting them.…”
Section: Introductionmentioning
confidence: 99%